Culture, Economy and Politics - Hesmondhalgh, David. author. aut Link
X, 235 p. 3 illus.
Keywords: This book focuses on cultural policy in the UK between 1997 and 2010 under the Labour party (or 'New Labour', as it was temporarily rebranded). It is based on interviews with major figures and examines a range of policy areas including the arts, creative industries, copyright, film policy, heritage, urban regeneration and regional policy.